The Ran GTPase-Activating Protein (RanGAP1) is critically involved in smooth muscle cell differentiation, proliferation and migration following vascular injury: implications for neointima formation and restenosis - Vorpahl, Marc Michael; Flotho, Annette; Melchior, Frauke; Wessely, Rainer (PLOS ONE, 2014)
Differentiation and dedifferentiation, accompanied by proliferation play a pivotal role for the phenotypic development of vascular proliferative diseases (VPD), such as restenosis. Increasing evidence points to an essential role of regulated nucleoporin expression in the choice between differentiation and proliferation. However, whether components of the Ran GTPase cycle, which is of pivotal importance for both nucleocytoplasmic transport and for mitotic progression, are subject to similar regulation in VPD is currently unknown. Here, we show that differentiation of human coronary artery smooth muscle cell (CASMC) to a contractile phenotype by stepwise serum depletion leads to significant reduction of RanGAP1 protein levels. The inverse event, dedifferentiation of cells, was assessed in the rat carotid artery balloon injury model, a well-accepted model for neointima formation and restenosis. As revealed by temporospatial analysis of RanGAP1 expression, neointima formation in rat carotid arteries was associated with a significant upregulation of RanGAP1 expression at 3 and 7 days after balloon injury. Of note, neointimal cells located at the luminal surface revealed persistent RanGAP1 expression, as opposed to cells in deeper layers of the neointima where RanGAP1 expression was less or not detectable at all. To gain first evidence for a direct influence of RanGAP1 levels on differentiation, we reduced RanGAP1 in human coronary artery smooth muscle cells by siRNA. Indeed, downregulation of the essential RanGAP1 protein by 50% induced a differentiated, spindle-like smooth muscle cell phenotype, accompanied by an upregulation of the differentiation marker desmin. Reduction of RanGAP1 levels also resulted in a reduction of mitogen induced cellular migration and proliferation as well as a significant upregulation of the cyclin-dependent kinase inhibitor p27KIP1, without evidence for cellular necrosis. These findings suggest that RanGAP1 plays a critical role in smooth muscle cell differentiation, migration and proliferation in vitro and in vivo. Appropriate modulation of RanGAP1 expression may thus be a strategy to modulate VPD development such as restenosis.